The screening of the presence of cryptosporidium spp. Oocyst in cow dung in Kuala Pilah / Nur Rillis Aniruddin - Aniruddin, Nur Rillis (2016)
Studies were initiated to determine the presence of Cryptosporidium spp. oocyst in cow dung and to study the morphology and characteristics of the oocyst. The cows are abundance in Kuala Pilah especially along the Beting streets and dungs may result in cryptosporidiosis outbreak which could affect human health. 60 stool samples were randomly collected from cattle in Kuala Pilah vicinity. The samples were then examined using modified formalin-ether concentration technique to recover the oocyst. The modified Ziehl-Neelsen staining was performed to each sample for oocysts identification. Out of the 60 dung samples examined, few samples gave positive result by the modified Ziehl-Neelsen staining method. The oocyst seemed to be in round and spherical appearance which is 4 to 6 microns diameter with some degree of red staining. To date, there were no reported on the present of Cryptosporidium spp. oocyst among farm animal in Kuala Pilah and this is the first positive result on the present of Cryptosporidium oocyst from cow dung screening especially along Beting streets, Kuala Pilah.